Factors affecting digital game addiction and physical activity attitudes and behaviors of adolescents - Gülbetekin, Eda; Güven, Erkan; Tuncel, Oğuzhan (Journal of Dependence, 2021)
Objective: This study aims to determine the factors that affects the adolescents' digital game addiction, physical activity attitudes and behaviours.Method: The descriptive study was conducted in Iğdır among 583 adolescent children living in the province of Iğdır. IDemographic Information Form, Cognitive Behavioral Physical Activity Scale and Digital Game Addiction Scale for Children were used to collect the data. The data were obtained through online interviews.Results: The study group consisted of 52.3% (n = 305) female and 47.7% (n = 278) male adolescents in totalParticipants' physical activity attitudes, depending on their gender, the duration of using the devices and the status of any sport they are interested in, on the other hand, digital game addictions are gender, place of residence, ownership of a digital tool, being a game they play constantly, the time they use the devices and the sport they are interested in. A weak and negative relationship was found between the total score of the Cognitive Behavioral Physical Activity Scale and the total score of the Digital Game Addiction Scale for Children.Conclusion: Children who are supported for the sports and who has backdrop can change their behaviour and attitudes towards physical activity, so game addictions can be reduced.
Keywords: Adolescent; digital game; physical activity